MiR-99 Family of Exosomes Targets Myotubularin-related Protein 3 to Regulate Autophagy in Trophoblast Cells and Influence Insulin Resistance - Shao-Xiao Liu; Yang Lv (Journal of Physiological Investigation)
The global incidence of gestational diabetes mellitus (GDM) continues to rise and is associated with negative outcomes in pregnancy. This study aims to investigate how the miR-99 family of exosomes derived from the placenta targets myotubularin-related protein 3 (MTMR3) to trigger autophagy and alter insulin resistance (IR) in trophoblast cells. In this study, placenta-derived exosomes from plasma samples of patients with GDM and normal pregnant women were isolated to evaluate the expression levels of miR-99 family members (miR-99a, miR-99b, and miR-100) by quantitative real-time polymerase chain reaction. Furthermore, we used Targeted Scan prediction and dual luciferase reporter assays to identify a potential target of the miR-99 family. Finally, Western blotting, CCK8 assay, and glucose level measurement were used to confirm that the miR-99 family regulates autophagy in trophoblast cells through targeting potential targets, thereby affecting IR. Through comprehensive molecular biology techniques, our analysis revealed that, in contrast to normal pregnant women, the placenta-derived exosomes of women with GDM exhibited a significant downregulation of the miR-99 family. Moreover, MTMR3 emerged as a potential target of the miR-99 family, revealing a negative correlation with the levels of miR-99. An increase in MTMR3 expression impaired cellular autophagy and contributed to IR. Conversely, augmenting the miR-99 family can lead to a downregulation of MTMR3, promotion of cellular autophagy, and mitigation of IR. This research demonstrated that the expression of the miR-99 family was reduced in plasma exosomes of GDM. The miR-99 family can directly target MTMR3, leading to its downregulation. This process activated autophagy in trophoblast cells and enhances insulin sensitivity. Consequently, the miR-99 family holds potential as a therapeutic strategy for patients with GDM.